The Impact of Teacher Professional Development on EFL Teachers’ Instructional Practices and Students’ Academic Achievement - Karim, Sayit Abdul; Ermawati , Novi Ayu; Anggraini, Adellia Dinta; Radjaban, R. Yohanes; Matas, Gordan (Universitas Cokroaminoto Palopo, 2025)
This study investigates the influence of Teacher Professional Development (TPD) on EFL teachers’ instructional practices and their perceived effects on students’ academic achievement in the Indonesian context. Drawing on Guskey's model of teacher change, this quantitative research involved three English teachers at SMA BOPKRI 2 Yogyakarta who participated in a structured TPD initiative. Data were collected using a Likert scale questionnaire, and analyzed descriptively on the impact of Teacher Professional Development and their perceived effect on students' academic achievement. The findings revealed consistent positive changes across five indicators: professional growth, instructional practices, student-centered adjustment, student engagement, and academic achievement. The respondents reported that TPD may enhance their self-confidence, increase innovative teaching strategies, and improve responsiveness to student needs. Furthermore, the study found that instructional improvement had a clear motivational effect on students; previously passive learners became more engaged, confident, and enthusiastic about learning English. Teachers also perceived improvements in students’ academic performance across key skill areas, including speaking, writing, and comprehension. This shows that TPD programs not only enhance teachers' pedagogical capabilities but also lead to meaningful gains in the students' engagement and learning achievement.